NATO’S ROLE IN A NON-MILITARY CRISIS: NATO’S ROLE IN A NON-MILITARY CRISIS - Antonova, Mariela; Antonov, Stamen (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The article analyzes NATO’s role in managing non-military crises, emphasizing its adaptation to modern security challenges such as pandemics, natural disasters, and cyber threats. It outlines the strategic framework of NATO’s crisis management, its cooperation with the EU and the UN, and its increasing involvement in humanitarian and civil protection operations. The study argues that NATO’s approach reflects a transformation from a traditional defense alliance to a multidimensional security actor focused on resilience and stability.